Needs analysis for the development of an Integrated Psychospiritual-Quranic Arabic Language Module (INPAQ Module) for juvenile rehabilitation - Wan Mohammad, Wan Azman; Zailani @ Hj Ahmad, Suhaila; Abu Bakar, Kaseh; Hassan, Siti Aishah; Zainal, Hakim; Mohmad Rouyan, Nurazan (Universiti Sultan Azlan Shah, 2024)
The Arabic language teaching at Henry Gurney School in Malaysia falls short of meeting the needs of juvenile rehabilitation, particularly in nurturing their aspiration to engage with religious instruction for self-development. This study aims to develop an Integrated Psychospiritual-Quranic Arabic Language Module (INPAQ Module) tailored specifically for juvenile rehabilitation. A case study design involving individual and focused group semi-structured interviews (n=21) was employed to examine the pressing need for developing an INPAQ module. The finding recognizes the Quranic Arabic language as a medium for enhancing the psychospiritual aspects of juvenile students. Informants’ responses indicate that juveniles’ motivation to learn Arabic language stems from their desire to strengthen their connection with divinity through understanding Quranic verses, dhikr, and prayer. However, the current approach to teaching Arabic language does not fully meet their needs. In light of these findings, restructuring the existing Arabic curriculum is crucial to better align with the aspirations and rehabilitative needs of juveniles. The development of INPAQ Module represents an initiative designed to improve current practices. The study, therefore, proposes further exploration of the INPAQ Module framework, specifically designed to address the rehabilitation needs of juveniles.